Effectiveness of Health Protocol Discipline at Universitas Terbuka Jayapura - Muhammad, Rivaldhy Nur; Sawir, Lestari Wulandari; Qomarrullah, Rif’iy (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this research is to measure and analyze the level of effectiveness of the health protocol discipline within the Universitas Terbuka of Jayapura City, Papua during the new normal period of Covid-19. This type of research uses observational analytic with a cross sectional design, carried out in January 2022 involving 115 student respondents. The research instrument used a questionnaire and data was collected online using the Google Forms application. Then the data was processed using univariate and bivariate analysis and Chi Square test using SPSS 25 software. The results of this study indicate that the variables age (P=0.214), gender (P=0.375), domicile (P=0.114), obedience (P=0.002), achievements and goals (P=0.016), attitude and personality (P=0.078), prevention system, responsibility (P=0.026), facility (P=0.085), and motivation (P=0.058). The conclusion is that there is no relationship between the variables age, gender, and domicile, but there is a relationship between the variables obedience, achievements and goals, attitude and personality, prevention system, responsibility, facility, and motivation with the level of effectiveness of the health protocol discipline. Therefore, several things that should be emphasized are the discipline of wearing masks, physical and social distancing, then washing hands and maintaining a clean and healthy lifestyle.